Resonance absorption, reflection, transmission of phonons and heat transfer through interface between two solids - Kosevich, Yu.A.; Feher, A.; Syrkin, E.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The different mechanisms of resonant transport of phonons between two media in the presence of impurity intermediate layer are described. Particular attention is focused on the resonance interaction of elastic waves with a two-dimensional defect on the contact boundary between two solids, on the multichannel interface phonon scattering and on the experimentally observed nonmonotonic temperature dependence of the reduced heat flux. In the cases when there is a direct interaction between edge atoms of the matrix as non-nearest neighbors or when the impurities do not fill completely the 2D interface layer, the additional channel for the transmission of phonons through the interface opens. This additional transmission channel manifests itself as a transmission (or reflection or absorption) peak with an asymmetric line shape (the so-called Fano resonance for phonons due to interference between the two transmission channels). Some applications of the Fano effect in magnon heat conductivity are also discussed.